2022
DOI: 10.1097/01.hjh.0000837740.17263.ec
|View full text |Cite
|
Sign up to set email alerts
|

25(oh)d as a Risk Factor of Essential Arterial Hypertension Considering the Genes Polymorphism Agtr1 (Rs5186) and VDR (Rs2228570)

Abstract: Objective:Essential arterial hypertension (EAH) remains the most common global non-communicable disease. More than 50% of patients with hypertension have additional cardiovascular risk factors. The aim of this study is to establish the role of 25-hydroxyvitamin D as an additional risk factor of EAH depending on 1166A>C polymorphism of AGTR1 gene (rs5186) and A/G polymorphism of VDR gene (rs2228570).Design and method:100 subjects with EAH and target-organ damaging (2nd stage), moderate, high, very high cardiova… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
0
0
2
Order By: Relevance
“…In the study conducted in the Kazakh population, the G/G genotype by rs3803662 polymorphism was statistically less common in tumors with high proliferative activity (immunohistochemical marker . In contrast to these data, some studies found no statistically significant differences between histopathological characteristics and molecular subtypes of breast cancer in the groups of patients with different histological types of breast adenocarcinomas and genotypically detected polymorphisms (Ahearn et al, 2019;Nuruev et al, 2023;Semianiv et al, 2021).…”
Section: Discussionmentioning
confidence: 86%
“…In the study conducted in the Kazakh population, the G/G genotype by rs3803662 polymorphism was statistically less common in tumors with high proliferative activity (immunohistochemical marker . In contrast to these data, some studies found no statistically significant differences between histopathological characteristics and molecular subtypes of breast cancer in the groups of patients with different histological types of breast adenocarcinomas and genotypically detected polymorphisms (Ahearn et al, 2019;Nuruev et al, 2023;Semianiv et al, 2021).…”
Section: Discussionmentioning
confidence: 86%
“…Despite reliable data supporting the need for screening to prevent rupture and reduce mortality in patients with AAA, the condition continues to pose a serious risk (15,(26)(27)(28). Screening is economically effective, even with an AAA prevalence as low as 0.5 % (4).…”
Section: Discussionmentioning
confidence: 99%
“…Критерії включення і невключення наведені у наших попередніх публікаціях [9][10][11][12][13][14][15]. Вік хворих коливався від 45 до 70 років (у середньому -59,87±7,98 року), серед них чоловіків -25,0%, жінок -75,0%.…”
Section: матеріали та методиunclassified
“…Висновки. Ризик розвитку метаболічних розладів зростає у хворих на есенційну артеріальну гіпертензію із Т-алелем гена GNB3 (825С>T) у 8,5 раза за найнижчої ймовірності таких змін у носіїв 12; p=0,048].…”
unclassified